1994
DOI: 10.1128/iai.62.12.5424-5433.1994
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and immunological characterization of the extracellular galactomannan of Aspergillus fumigatus

Abstract: The galactomannan (GM) produced extracellularly by Aspergillus fumigatus has been purified by a double sequential hydrazine-nitrous acid treatment of the ethanol precipitate of the culture filtrate. Nuclear magnetic resonance and gas-liquid chromatography-mass spectrometry analysis have been performed on intact GM, acid-hydrolyzed GM, and oligomers resulting from the acetolysis of the acid-hydrolyzed GM. Results show that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(147 citation statements)
references
References 45 publications
1
144
1
1
Order By: Relevance
“…The EBA2 was raised against extracellular galactomannan (GM) from the pathogenic fungus Aspergillus fumigatus [19]. GM was subsequently characterised and shown to be composed of a linear mannan core with side chains of up to ¢ve L-1,5-linked Galf units [3]. The mannan core is not antigenic.…”
Section: Resultsmentioning
confidence: 99%
“…The EBA2 was raised against extracellular galactomannan (GM) from the pathogenic fungus Aspergillus fumigatus [19]. GM was subsequently characterised and shown to be composed of a linear mannan core with side chains of up to ¢ve L-1,5-linked Galf units [3]. The mannan core is not antigenic.…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme purification. Mycelial culture of A. fimigatus, strain CBS 143-89 and preparation of cell wall autolysate were carried out as previously described (LatgC et al, 1994;Hartland et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…b-Galactofuranosyl residues have been shown to be a component of the galactomannan produced by Aspergillus spp. [31,41], the O-linked glycan of A. niger GAM [20,23], invertase secreted by A. nidulans [27] and part of other fungal glycoproteins [32,42,43]. Takayanagi et al [9] also observed the, to date, novel structure of a-linked Galf residues on a different a-galactosidase produced by A. niger.…”
Section: Biological Significancementioning
confidence: 99%